Pyrite alteration and neoformed magnetic minerals in the fault zone of the Chi‐Chi earthquake (Mw7.6, 1999): Evidence for frictional heating and co‐seismic fluids - Yu‐Min Chou; Sheng‐Rong Song; Charles Aubourg; Yen‐Fang Song; Anne‐Marie Boullier; Teh‐Quei Lee; Mark Evans; En‐Chao Yeh; Yi‐Ming Chen (Geochemistry, Geophysics, Geosystems)
During an earthquake, physical and chemical transformations lead to alteration and formation of minerals in the gouge layer. Altered and neoformed minerals can be used as tracers of some earthquake processes. In this study, we investigate pyrite and magnetic minerals within the host Chinshui siltstone and the 16‐cm‐thick gouge. This gouge hosts the principal slip zone of Chi‐Chi earthquake (Mw7.6, 1999). In the Chinshui siltstone, pyrite framboids of various sizes and euhedral pyrite are observed. The magnetic mineral assemblage comprises stoichiometric magnetite, greigite, and fine‐grained pyrrhotite. The pyrite content is generally reduced in the gouge compared to the wall rock. The magnetic mineral assemblage in the gouge consists of goethite, pyrrhotite, and partially oxidized magnetite. The pyrrhotite, goethite and some magnetite are neoformed. Pyrrhotite likely formed from high temperature decomposition of pyrite (>500°C) generated during co‐seismic slip of repeated earthquakes. Goethite is inferred to have formed from hot aqueous co‐seismic fluid (>350°C) in association with the 1999 Chi‐Chi event. Elevated fluid temperatures can also explain the partial alteration of magnetite and the retrograde alteration of some pyrrhotite to pyrite. We suggest that characterization of neoformed magnetic minerals can provide important information for studying earthquake slip zones in sediment‐derived fault gouge.